Characterization of a novel metastatic prostate cancer cell line of LNCaP origin. Issue 2 (26th October 2015) - Castanares, Mark A.; Copeland, Ben T.; Chowdhury, Wasim H.; Liu, Minzhi M.; Rodriguez, Ronald; Pomper, Martin G.; Lupold, Shawn E.; Foss, Catherine A.
Abstract : BACKGROUND: The LNCaP cell line was originally isolated from the lymph node of a patient with metastatic prostate cancer. Many cell lines have been derived from LNCaP by selective pressures to study different aspects of prostate cancer progression. When injected subcutaneously into male athymic nude mice, LNCaP and its derivatives rarely metastasize. METHODS: Here, we describe the characteristics of a new LNCaP derivative, JHU‐LNCaP‐SM, which was generated by long term passage in normal cell culture conditions. RESULTS: Short tandem repeat (STR) analysis and genomic sequencing verified JHU‐LNCaP‐SM derivation from parental LNCaP cells. JHU‐LNCaP‐SM cells express the same mutated androgen receptor (AR) but unlike LNCaP, are no longer androgen dependent for growth. The cells demonstrate an attenuated androgen responsiveness in transcriptional assays and retain androgen sensitive expression of PSA, AR, and PSMA. Unlike parental LNCaP, JHU‐LNCaP‐SM cells quickly form subcutaneous tumors in male athymic nude mice, reliably metastasize to the lymph nodes and display a striking intra‐tumoral and spreading hemorrhagic phenotype as tumor xenografts. CONCLUSIONS: The JHU‐LNCaP‐SM cell line is a new isolate of LNCaP, which facilitates practical, preclinical studies of spontaneous metastasis of prostate cancer through lymphatic tissues. Prostate 76:215–225, 2016 . © 2015 Wiley Periodicals, Inc.